Applications of Electromagnetic Waves in Medical Imaging and Biological Systems - Hussein, Hussein Allawi; Nasser, Sawsan Abd Al_Jabbar; Samir, Maher Safuk Nawaf; Ammash, Dalya Ibraheem; Mohammed, Ali Hashim (American Journal of Botany and Bioengineering, 2025)
Electromagnetic waves (EMWs) play a crucial role in advancing medical imaging and therapeutic applications, offering non-invasive and accurate diagnostic solutions. However, despite their wide adoption, a knowledge gap persists in fully understanding the interaction mechanisms between EMWs and biological tissues, especially in emerging imaging modalities. This article reviews the principles and recent advancements in electromagnetic-based imaging techniques, including MRI, CT, ultrasound, microwave imaging, photoacoustic imaging, and terahertz imaging. The study also examines the therapeutic potentials of EMWs, such as in hyperthermia, magnetic field therapy, and radiation therapy. Findings highlight that EM-based technologies significantly enhance spatial resolution, real-time imaging capabilities, and diagnostic accuracy while reducing patient risk compared to ionizing radiation methods. Nevertheless, challenges related to safety standards, exposure limits, and optimization of EMW-tissue interaction remain. The results suggest that interdisciplinary research integrating physics, biomedical engineering, and AI will be essential to unlock the full potential of EM-based medical applications.